UJI EFEKTIVITAS JAMUR ANTAGONIS Trichoderma sp. dan Gliocladium sp. UNTUK MENGENDALIKAN PENYAKIT LANAS (Phytophthora nicotianae) PADA TANAMAN TEMBAKAU DELI (Nicotiana tabaccum L.) - Irma Agustina; Mukhtar Iskandar Pinem; Fatimah Zahara (Jurnal Agroekoteknologi, 2013)
The test of the effectiviveness of Trichoderma sp. and Gliocladium sp. antagonism fungi is aimed tocontrol lanas disease (Phytophthora nicotianae) in Deli tobacco plants (Nicotiana tabaccum L.). Theaim of the research was to know the effectiveness of Trichoderma sp. andGliocladium sp.antagonism fungi in controlling lanas disease in Deli tobacco plants. The research wasconducted at Tembakau Deli Research Center of PTPN II Sampali, Medan, from May untilSeptember, 2012. The research used non-factorial RAK (cluster random design) with ten treantmentsand three repetitions: control, P.nicotianae, 5 grams of Trichoderma sp., 10 grams of Trichoderma sp.,15 grams of Trichoderma sp., 20 grams of Trichoderma sp., 5 grams of Gliocladium sp.,10 grams of Gliocladium sp., 15 grams of Gliocladium sp., and 20 grams of Gliocladium sp. The resultof the research showed that the percentage of the highest attack was found in the treatment ofP.nicotianae (25.00%), but there was no symptom (0,00%) in the treatments of control,15 grams of Trichoderma sp., 20 grams of Trichoderma sp., 10 grams of Gliocladium sp.,15 grams of Gliocladium sp., and 20 grams of Gliocladium sp. The highest plant was found in thetreatment of 20 grams of Gliocladium sp. (50,92 centimeters) and the lowest plant was found in thetreatment of P.nicotianae (31,14 centimeters). The largest number of leaves was found in treatment of20 grams of Gliocladium sp. (20,18 leaves), and the smallest number of leaves was found in thetreatment of P.nicotianae (9,25 leaves). The result of the test of Trichoderma sp. and Gliocladium sp.antagonism fungi on P.nicotianae indicated that the growth of both fungi had rapidly developed so thatP.nicotianae tended to get away from antagonism at the media in the laboratory.Keywords: Trichoderma sp., Gliocladium sp., P.nicotianae, Antagonism